Fetal Cortical Transplants in Adult Rats Subjected to Experimental Brain Injury. (1991) - Soares, Holly; McIntosh, Tracy K.
Abstract : Fetal cortical tissue was injected into injured adult rat brains following concussive fluid percussion (FP) brain injury. Rats subjected to moderate FP injury received E16 cortex transplant injections into lesioned motor cortex 2 days, 1 week, 2 weeks, and 4 weeks post injury. Histological assessment of transplant survival and integration was based upon Nissl staining, glial fibrillary acidic protein (GFAP) immunocytochemistry, and staining for acetylcholinesterase. In addition to histological analysis, the ability of the transplants to attenuate neurological motor deficits associated with concussive FP brain injury was also tested. Three subgroups of rats receiving transplant 1 week, 2 weeks, and 4 weeks post injury Were chosen for evaluation of neurological motor function. Fetal cortical tissue injected into the injury site 4 weeks post injury failed to incorporate with injured host brain, did not affect glial scar formation, and exhibited extensive GFAP immunoreactivity. No improvement in neurological motor function was observed in animals receiving transplants 4 weeks post injury. Conversely, transplants injected 2 days, 1 week, or 2 weeks post injury survived, incorporated with host brain, exhibited little GFAP immunoreactivity, and successfully attenuated glial scarring. However, no significant improvement in motor function was observed at the one week or two week time points. The inability of the transplants to attenuate motor function may indicate inappropriate host/transplant interaction. Our results demonstrate that there exists a temporal window in which fetal cortical transplants can attenuate glial scarring as well as be successfully incorporated into host brains following FP injury.